ANALISIS KESULITAN GURU IPS DALAM MENYUSUN PERANGKAT PEMBELAJARAN DI SMP NEGERI KECAMATAN IBU - Jainudin Hasim (Jurnal Geocivic, 2018)
Researching aims to know the ability of teachers in drafting device of learning in Junior High School the country Mother Subdistrict of West Halmahera Regency.this is a descriptive study with a qualitative approach. The population in this research, is a teacher-teacher Mother in Subdistrict 5 IPS schools with numbered 8 teachers. Engineering data collection i.e. observation, interview and documentation.The validity of the data in this study using triangular techniques i.e. checking from a variety of sources in different ways. Qualitative data analysis techniques, namely, the reduction of the data, the presentation of the data, and draw conclusions. Based on the results of the it can be concluded that: the ability of a teacher in drawing up a learning device in Sub junior's mother is still having difficulty in integrating various social material into SK/KD/indicators as well as the selection of appropriate learning materials.Keywords: teacher trouble, IPS, Device learning